An imperious, closed sandbox? A rejoinder to Van Dijk's critique of the framing perspective on social movement mobilization. (April 2023) - Snow, David A; Vliegenthart, Rens
In this article, we provide a response to Teun van Dijk's criticism of the framing perspective on social movements, as expressed in his article 'Analyzing Frame Analysis. A Critical Review of Framing Studies in Social Movement Research'. We argue that a more constructive tone is warranted and explain how his criticism is largely based on a selective reading and misinterpretation of the vast literature on framing and social movements. We provide a more detailed explanation of how discourse and related concepts such as schema and ideology are discussed by social movement scholars and critically reflect on his claim that framing as a concept can rather be replaced by discourse and/or various other cognitive/psychological constructs. Finally, we suggest how a discourse perspective and insights from social movement framing can be complementary in increasing our understanding of how movements (and other actors) communicate and with what consequences.